2017
DOI: 10.1158/1538-7445.am2017-2524
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2524: MiR-124 suppresses p62 and p65/NFkB to regulate autophagy, inflammation and cell death in KRAS mutant mesenchymal NSCLC cells

Abstract: Background KRAS mutant non-small cell lung cancers (NSCLC) are molecularly and histologically diverse. Epithelial-like cells are more KRAS dependent, whereas mesenchymal-like cells are less KRAS dependent. These two subtypes are designated KE (epithelial) and KM (mesenchymal), respectively. A KE versus KM subtype transcriptional signature reveals specific modes of KRAS dependent survival signaling in the KE subtype. This KRAS dependency signature is significantly enriched with predicted microRNA (miRNA) target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In agreement with our findings, miR-124 was recently reported to regulate autophagy, inflammation, and cell death via targeting p62 and p65/NF-κB in KRAS mutant mesenchymal NSCLC cells. 35 In addition, Sun et al 15 revealed that miR-124 upregulation attenuated cancer cell migration and NF-κB pathway hindered miR-124 expression in non-small-cell lung cancer. Therefore, more research about the regulatory relationship between miR-124 and NF-κB in NPC are needed in future work.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our findings, miR-124 was recently reported to regulate autophagy, inflammation, and cell death via targeting p62 and p65/NF-κB in KRAS mutant mesenchymal NSCLC cells. 35 In addition, Sun et al 15 revealed that miR-124 upregulation attenuated cancer cell migration and NF-κB pathway hindered miR-124 expression in non-small-cell lung cancer. Therefore, more research about the regulatory relationship between miR-124 and NF-κB in NPC are needed in future work.…”
Section: Discussionmentioning
confidence: 99%